(untitled) (KULT_online, 2013)
This recently released handbook of cultural philosophy is a well thought-out and coherently conceptualized book with informative contributions that are worth reading. In a chronological section, essential classical positions of cultural philosophy are introduced, from Giambattista Vico to Richard Rorty. Supplementing this is an alphabetical dictionary with categories and concepts such as society and time. The volume proves to be both a useful reference work and an engrossing read.